Respirable Particles and Gas Contaminants Emissions from a Desktop Laser Cutter and Engraver - Kevin O’Neill; Xinyi Niu; Jun Wang; Runcheng Fang (Aerosol and Air Quality Research)
Abstract Airborne contaminants produced during the laser cutting processes are hazardous substances produced as byproducts during laser cutting or engraving operations. These contaminants include respirable particulates, volatile organic compounds (VOCs), and other toxic substances that pose health risks to humans. As desktop laser cutting/engraving technology gains popularity, addressing the potential health hazards associated with airborne contaminants is critical. This study aimed to evaluate the concentrations of respirable particles, sub-half-micron particles, VOCs, and carbon monoxide (CO) that are emitted during laser cutting or engraving processes. The experimental matrix consisted of four materials (cardboard, wood, plastic, and glass) and three currents (10 amp, 15 amp, 20 amp), while also assessing the efficiency of exhaust ventilation. The results showed that the interaction of materials, currents, and ventilation significantly influenced emission concentrations of respirable particulate matter. Cardboard consistently exhibited the highest concentration of respirable particulate matter of 253.9 ± 47.6 mg m–3 and an average emission rate of sub-half-micron particles of 5.8 × 1010 # min–1, characterized by the smallest geometric mean diameter of 53 nm in the absence of ventilation. The extremely high emission highlighted the potential of ultrafine particle exposures and health risks from cutting cardboard. Conversely, glass demonstrated excellent resilience to thermal cutting, resulting in lower particle emissions. Wood and plastic materials showed intermediate levels of respirable and ultrafine particle production compared to cardboard and glass. Materials with higher carbon content, such as wood and cardboard, generated higher levels of VOCs and CO, compared to plastic (high VOC but no CO emissions) and glass (no VOC nor CO emission). Additionally, implementing ventilation control during laser cutting or engraving processes is highly recommended, as it effectively reduces the emissions of respirable particles and completely removes gaseous contaminants.